A STUDY OF DISTRIBUTION OF VARIOUS CAUSES OF BLINDNESS AMONGST PATIENTS ATTENDING AT TERTIARY EYE CARE HOSPITAL FOR VISUAL HANDICAP CERTIFICATE PURPOSE - NAGASRI, KURAPATI BHANU; JYOTHI, PAMU NIRMALA; MADHAVI, MALLULA (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: To study the various causes of blindness among patients attending the DR.R.S.P.R. Government Regional Eye Hospital, Visakhapatnam, for visual handicap certificates. To understand the relationship between age and sex with various etiologies. Methods: Retrospective analysis of records of 272 patients (360 eyes) who had applied for the visual handicap certificate in the period of 1 year, i.e., from August 2021 to July 2022, at DR. R. S. P. R. Government regional eye hospital, Visakhapatnam. Certificates were issued after all the necessary examinations and investigations were done by qualified ophthalmologists, as per the guidelines. Results: The majority are in the 31–50 age group (41.8%). Males (69.85%) are more than females (30.14%). Preventable causes (52.7%) are more common than non-preventable causes (47.2%). Phthisis (17.2%) was the most common preventable cause, followed by corneal opacity (13.3%). Retinitis pigmentosa (20.5%) was the most common non-preventable cause. Conclusion: Most common causes of blindness are preventable, so early diagnosis, prompt treatment, and regular follow-up reduce the incidence of blindness. Awareness programs for preventable blindness, health education, and genetic counseling for congenital and hereditary causes will definitely decrease the incidence of blindness.